Espectroscopia de fluorescência aplicada ao estudo das interações de formação de nanoestruturas de peptídeos contendo maguemita - Dias, Diogo Lopes (2014)
This work aims at preparation and morphological and photophysical characterization of systems consisting of self-assembled structures based on the L-diphenylalanine dipeptide doped with magnetic and luminescent aditives. In this way, nanoparticles magnetic particles of maghemite (γ-Fe2O3) were prepared and used as magnetic additives, while Cadmium Telurium (CD and Te) - based Quantum Dots (QD) were employed as the luminescent additive. The resulting system was characterized by scanning electron microscopy and steady-state fluorescence spectroscopy techniques and their properties were compared tothose presented by the individual components and the intermediate systems. Also, a study on the interaction forces involved in the self-organization of the dipeptide was carried out by varying the method of preparation by employing in the preparation, solvents with distinct physical-chemical properties and by relating conformational differences in the nano and micro structures obtained in each preparation protocol with the balance of interactions forces that contribute to the self-assembling phenomenon. Regarding- to that, when self-assembling is promoted in solvents with distinct polarizabilities (Δf), as obtained by Lippert equation, it is possible to infer about the forces balance that are predominant. The peculiarities of each structure obtained were explored by SEM imaging and spectroscopic data. From scanning electron micrographs, it is observed that self-assembling is governed by interactions between neighboring aromatic rings, trhough π-stacking interactions and generates, in most cases, tubular structures. However, in certain protocols, lamellar structures were observed. When self-assembilng occurs in water, L-diphenylalanine (NT-F-F) nanotube growth occursfrom a starting site and develops in all directions. The use of additives with distinct properties acted in self-assebling process, favoring it when the quantum dot is additive or disfavoring it when the magnetic nanoparticles are the additives. Furthermore, it was observed that in the system containing both additives in proportions in which aggregates are not observed, nanotube´s self-asembling and their further association leaded to microtubes. Structural differences between obtained NT-F-F allow us to infer on the nature of interactions between the dopants and the NT-F-F. The photophysical behavior analysis revealed that the fluorescence emission increases due to the nature of interaction between QD and NT-F-F, to give rise to a charge transfer complex. These results indicate that there may be a conjugation xxiii effect favoring luminescent processes from relaxed energy states of the system containing the magnetic particle and QD as additives, simultaneously.